Natural Killer Cells as Helper Cells in Dendritic Cell Cancer Vaccines - Pampena, María Betina; Levy, Estrella Mariel (Frontiers in Immunology, 2015)
Vaccine-based cancer immunotherapy has generated highly variable clinical results due to differing methods of vaccine preparation and variation in patient populations, among other lesser factors. Moreover, these clinical responses do not necessarily correspond with the induction of tumor-specific cytotoxic lymphocytes. Here we review the participation of natural killer (NK) cells as alternative immune components that could cooperate in successful vaccination treatment. NK cells have been described as helper cells in dendritic cell-based cancer vaccines, but the role in other kinds of vaccination strategies (whole cells, peptide or DNA- based vaccines) is poorly understood. In this article we address the following issues regarding the role of NK cells in cancer vaccines: NK cell anti-tumor action sites, and the loci of NK cell interaction with other immune cells; descriptions of new data on the memory characteristics of NK cells described in infectious diseases; and finally phenotypical and functional changes after vaccination measured by immunomonitoring in preclinical and clinical settings.